The constraints and affordances of co-creation as a teaching strategy within a Project Based Learning Program - Candy, Nicole (My University, 2022)
Co-creation refers to the meaningful collaboration between teachers and learners. This study investigated co creation as a teaching strategy, by questioning how co-creation influenced Grade 8 and 9 learners’ motivation to engage in PBL lessons, and whether sustained engagement was achieved through co-creation. Of interest was whether there were any skill gaps that impact on a learner’s ability to successfully engage in co-creation. This qualitative, case study involved a complex research design, divided into three stages. The first stage involved the learners completing a traditional PBL project that was designed by their teachers. The process of co-creation was then implemented as a teaching strategy, and learners collaborated with their teachers to design a PBL project that they would like to undertake. Once the co-creation projects were designed, learners had the opportunity to complete their own project or the project of a peer. After choosing, learners had to complete their projects. Questionnaires were used as a means of gathering data at different stages throughout the research process. The first questionnaire was completed by learners and teachers at the end of the traditional PBL project and another was completed by learners and teachers at the end of the project that had been designed through the co-creation process. The key findings of the study were that the characteristics of traditional PBL that enhance learner motivation are present during projects that have been co-created. Additional characteristics of the co-creation process that improve motivation are the increase in learner choice and autonomy. In terms of learner engagement, co-creation achieved higher levels of sustained engagement and engagement towards the end of the project, than were shown in traditional PBL. However, learner engagement in the middle of a co-creation project was noted to be lower than traditional PBL. Learners’ skills that require development in order to complete a co-creation project successfully included: research skills, IT skills, time management and reflection. The main finding of the study was that co-creation should be incorporated into a PBL program, but that this process needed to be scaffolded in order to be implemented successfully. This scaffolding process needed to include additional support provided to learners when researching or implementing the use of technology. It is also recommended that teachers introduce co-creation in sections of a project, before allowing learners to co-create an entire project.
This dissertation has been submitted in fulfillment of the requirements of Masters of Education to the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, 2022